Optimization Study of Pneumatic–Electric Combined Braking Strategy for 30,000-ton Heavy-Haul Trains - Mingtao Zhang; Congjin Shi; Kun Wang; Pengfei Liu; Guoyun Liu; Zhiwei Wang; Weihua Zhang (Actuators)
The normalized operation of 30,000-ton heavy-haul trains is of significant importance for enhancing the transportation capacity of heavy-haul railways. However, with the increase in train formation size, traditional braking strategies result in excessive longitudinal impulse when combined pneumatic and electric braking is applied on long, steep gradients. This presents a serious challenge to the braking safety of the train. To this end, this paper establishes a longitudinal dynamic model of a 30,000-ton heavy-haul train based on vehicle system dynamics theory, and validates the model’s effectiveness through line test data. On this basis, the influence of two braking parameters, namely, the distribution of the magnitude of the electric braking force and the matching time of pneumatic braking and electric braking, on the longitudinal dynamic behavior of heavy-haul trains is studied. Thereby, an optimized combined pneumatic and electric braking strategy is formulated to reduce the longitudinal impulse of the trains. The results show that setting reasonable braking parameters can effectively reduce the longitudinal impulse, with the braking matching time having a significant impact on the longitudinal impulse. Specifically, when using a strategy where the electric braking forces of three locomotives are set to 90 kN, 300 kN, and 300 kN, with a 30 s delay in applying the electric braking force, a better optimization effect is achieved. The two proposed braking strategies reduce the maximum longitudinal forces by 20.27% and 47.83%, respectively, compared to conventional approaches. The research results provide effective methods and theoretical guidance for optimizing the braking strategy and ensuring the operational safety of 30,000-ton heavy-haul trains.